2014
DOI: 10.1111/aor.12362
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Emotional Distress Early After Left Ventricular Assist Device Implant: A Mixed-Method Study

Abstract: Patients who temporarily or permanently rely on left ventricular assist devices (LVADs) for end-stage heart failure face complex psychological, emotional, and relational problems. We conducted a mixed-method study to investigate quality of life, psychological symptoms, and emotional and cognitive reactions after LVAD implant. Twenty-six patients admitted to cardiac rehabilitation were administered quality of life questionnaires (Short Form 36 of the Medical Outcomes Study and Minnesota Living with Heart Failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
4
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 25 publications
(31 reference statements)
2
51
4
10
Order By: Relevance
“…Previous studies examining depression in patients with VADs have been cross-sectional 810 , or have included infrequent follow up over about 6–15 months 11, 12 . Mapelli and Modica’s studies demonstrated that after VAD implantation, patients experienced mild anxiety or depression without significant changes over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining depression in patients with VADs have been cross-sectional 810 , or have included infrequent follow up over about 6–15 months 11, 12 . Mapelli and Modica’s studies demonstrated that after VAD implantation, patients experienced mild anxiety or depression without significant changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important topic to examine as heart failure itself can have an effect on psychiatric health, in particular depression. 7 The literature on psychological symptoms in patients with VADs is restricted to depression, anxiety 812 , and post-traumatic stress disorder (PTSD), and the majority of these studies included only a small number of patients (e.g. a range of 14–30 patients).…”
Section: Introductionmentioning
confidence: 99%
“…25 Similar findings are reported in a mixed methods study in which improved quality of life was reported early after implantation but emotional distress remained high. 26 It should be noted that the current body of knowledge related to quality of life and emotional distress in the post implantation period remains limited. Additional studies addressing quality of life over time capturing individual change are needed including both general quality of life measures such as the European Quality of Life-5 Dimensions (EQ5D) and measures specific and sensitive to the LVAD population such as mixed methods and qualitative studies.…”
Section: Discussionmentioning
confidence: 99%
“…In order to make the interpretation of the two MLHFQ dimensions comparable, the physical and emotional dimension scores were standardized to 0-100 and reversed with higher scores indicating better quality of life. The MLHFQ is widely used in Italian studies (Giordano et al, 2013;Modica et al, 2015) and its validity and reliability has been established (Garin et al, 2013;Munyombwe et al, 2014). Reliability of the MLHFQ in this study resulted with a Cronbach's alpha of 0.89 for the physical dimension, 0.86 for the emotional dimension and 0.92 for the whole instrument.…”
Section: Quality Of Lifementioning
confidence: 60%